A fixed point result for mean nonexpansive mappings. (1st September 2020) - Reich, Simeon; Zaslavski, Alexander J.
Abstract : For a certain class of mean nonexpansive self-mappings of complete metric spaces, we show that all the iterates of each mapping in this class converge, uniformly on bounded subsets, to its unique fixed point.